Influence of a repeated peripheral electrical stimulation on substance P and cortisol concentrations, and behavior in German Simmental calves — a pilot study - Tschoner, Theresa; Kerber, Hannah; Zablotski, Yury; Knubben-Schweizer, Gabriela; Feist, Melanie (Frontiers in Veterinary Science, 2026)
ObjectiveThe aim was to assess plasma substance P (PSPC) and plasma cortisol (PCC) concentrations, vital signs, behavioral parameters, and activity in calves submitted to either an electrical, or a sham stimulus. The hypothesis of this pilot study was that an electrical stimulus increases plasma substance P concentrations in calves due to nociception.MethodsA total of 24 male calves (43.9 ± 2.0 days old) were included in this study. Calves in PAIN (n = 12) were submitted to 5 consecutive electrical stimuli, and calves in CON (n = 12) to 5 consecutive sham stimuli. Blood samples to measure PSPC and PCC were taken before (baseline and at 0 min), during (5 min to 25 min), and after (30 min to 7 hours) stimulation. Vital signs and behavior were recorded for 30 min during the stimulation and additionally before each blood sampling time. Activity was assessed over 24 h.ResultsThere were no significant differences in PSPC between groups. In PAIN, PSPC were significantly lower at 25 min compared with at baseline and at 0 min. PCC were significantly lower at 4.5 h compared with at baseline and at 0 min in CON. Calves in PAIN showed a significantly lower number of “ear movements,” but a significantly higher number of “shaking of the legs” during stimulation. Calves in PAIN showed significantly more occurrences of “head held below dorsal line” during stimulation, and significantly more occurrences of “eye lids half closed” during and after stimulation, compared with CON. Activity did not differ between groups.ConclusionAdministration of an electrical stimulus resulted in a decrease of PSPC compared to control animals, despite animals in PAIN showing behavior indicative of nociception. These results may affect the use of substance P as an objective biomarker for nociception for the assessment of pain in cattle from a stimulus that does not cause either tissue damage or inflammation.